PENGARUH TEKNIK MIND MAPPING BERBASIS MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 12 PADANG - Fadillah, Ummi; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three, namely, first, describing the writing skills of the report text of the observation of class VII students of SMP Negeri 12 Padang before using mind mapping techniques based on discovery learning models. Second, describe the writing skills of the report report observation text of grade VII students at SMP Negeri 12 Padang after using mind mapping techniques based on discovery learning models. Third, describing the effect of mind mapping techniques based on discovery learning models on the writing skills of the report's observation text in grade VII students at SMP Negeri 12 Padang. There are two data of this study, namely the score of the results of the test writing skills in the report text of the seventh grade students of SMP Negeri 12 before and after using the mind mapping technique based on the discovery learning model. Based on the results of the study, it was concluded three things, namely first, the writing skills of the report report observation text of class VII Padang 12 Public Middle School before using the mind mapping technique based on discovery learning models in the Enough qualifications (C) with an average value of 59.51. Second, the report writing skills of the observation results of the seventh grade students of SMP Negeri 12 Padang after using the mind mapping technique based on the discovery learning model are more than adequate (LdC) with an average value of 71.74. Third, there is a significant effect in the use of mind mapping techniques based on discovery learning models on the report writing skills of the observation results of class VII students at SMP Negeri 12 Padang because of the tcount> t table (4.91> 1.70).Â Kata kunci: Pengaruh, Teknik Mind Mapping, Model Discovery Learning, Laporan Hasil Observasi.